2015
DOI: 10.2105/ajph.2014.302251
|View full text |Cite
|
Sign up to set email alerts
|

Association of Campus Tobacco Policies With Secondhand Smoke Exposure, Intention to Smoke on Campus, and Attitudes About Outdoor Smoking Restrictions

Abstract: College campus tobacco-free policies are an emerging trend. Between September 2013 and May 2014, we surveyed 1309 college students at 8 public 4-year institutions across California with a range of policies (smoke-free indoors only, designated outdoor smoking areas, smoke-free, and tobacco-free). Stronger policies were associated with fewer students reporting exposure to secondhand smoke or seeing someone smoke on campus. On tobacco-free college campuses, fewer students smoked and reported intention to smoke on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
75
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 5 publications
8
75
0
2
Order By: Relevance
“…Lee, Ranney, and Goldstein () find that the campuses with high‐strength policies have fewer cigarette butts near selected building entrances than campuses with medium‐ or low‐strength policies and report no significant difference in the number of cigarette butts collected across campuses with low‐ and medium‐strength policies. Similar results are observed in Fallin, Roditis, and Glantz () which demonstrates an inverse relationship between reported exposure to secondhand smoke and observed smoking on campus and tobacco policy strength.…”
Section: Previous Literaturesupporting
confidence: 86%
See 1 more Smart Citation
“…Lee, Ranney, and Goldstein () find that the campuses with high‐strength policies have fewer cigarette butts near selected building entrances than campuses with medium‐ or low‐strength policies and report no significant difference in the number of cigarette butts collected across campuses with low‐ and medium‐strength policies. Similar results are observed in Fallin, Roditis, and Glantz () which demonstrates an inverse relationship between reported exposure to secondhand smoke and observed smoking on campus and tobacco policy strength.…”
Section: Previous Literaturesupporting
confidence: 86%
“…Lee, Ranney, and Goldstein (2013) find that the campuses with high-strength policies have fewer cigarette butts near selected building entrances than campuses with medium-or low-strength policies and report no significant difference in the number of cigarette butts collected across campuses with low-and medium-strength policies. Similar results are observed in Fallin, Roditis, and Glantz (2015) which demonstrates an inverse relationship between reported exposure to secondhand smoke and observed smoking on campus and tobacco policy strength. Lechner et al (2012) is quite similar to UCM's but, unlike our study, instead of counting the number of cigarette butts observed at a given hotspot, Lechner et al (2012) surveyed students over a 3-year period and compared smoking behavior to baseline survey results collected prior to the intervention.…”
Section: Previous Literaturesupporting
confidence: 82%
“…College campus smoke- and tobacco-free policies are being rapidly adopted nationwide. 8 These policies have been associated with reduced smoking rates 9 and exposure to secondhand smoke, 10 less cigarette butt litter, 11,12 and lower reported intention to smoke on campus. 10 Most faculty, students, 9 administrators, 13 and college and ‘university presidents support campus tobacco-free policies.…”
mentioning
confidence: 99%
“…Furthermore, previous studies have shown that a complete smoking ban on campus reduces cigarette consumption and smoking prevalence twice as much as a partial ban. 21,22 …”
Section: Commentmentioning
confidence: 99%